The Effect Of Short-Term Debt And Long-Term Debt on The Income of Palm Oil Stock Issuers - Umar; Rusmana Putri, Qisty Amalina; Dewi, Evi Retno C (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
This study aims to explore how short-term and long-term debt affect the operating income of palm oil companies. This study is a type of quantitative research using the panel data multiple regression analysis method. The independent variables in this study are Short-Term Debt (X1) and Long-Term Debt (X2). The dependent variable in this study is Operating Income (Y). The data source in this study is the Indonesia Stock Exchange Report in 2019-2023 and uses the Purposive Sampling Technique. The results of the study show that Short-Term Debt and Long-Term Debt partially do not have a significant effect on the Operating Income of Palm Oil Issuer Shares. In addition, simultaneously Short-Term Debt and Long-Term Debt have a significant effect on the Operating Income of Palm Oil Issuer Shares.